Sustainability and Gender Perspective in Food Innovation: Foods and Food Processing Coproducts as Source of Macro- and Micro-Nutrients for Woman-Fortified Foods - Estrella Sayas-Barberá; Jose Angel Pérez-Álvarez; Casilda Navarro-Rodríguez de Vera; Manuela Fernández-López; Manuel Viuda-Martos; Juana Fernández-López (Foods, 2022)
Micro- and macro-nutrient deficiencies among women are considered a global issue that the food industry has not adequately considered until recently. The industry must provide and guarantee a diversity of food products worldwide that allow women to get a correct and balanced diet according their life stage. The food industry must focus on this challenge within a framework of sustainable production, minimizing the use of natural resources and avoiding the emission of waste and pollutants throughout the life cycle of food. Food coproducts are presented as potential bioactive functional compounds which can be useful for technological purposes, due to the fact that they can serve as non-chemical, natural and health-improving food ingredients. In this review, we focus on the potential use of food processing coproducts which must be part of a strategy to promote and improve women’s health and well-being. This knowledge will make it possible to select potential ingredients from coproducts to be used in the fortification of foods intended for consumption by females and to introduce sustainability and gender perspectives into food innovation. The attainment of fortifications for foods for women has to be linked to the use of sustainable sources from food coproducts in order to be economically viable and competitive.